Caracterización de los residuos sólidos de la ciudad de Bellavista - Cubas Hernández, Elvis (2011)
This research work was carried out in the Bellavista city, San Martín department. Bellavista, is a city in the Peruvian jungle, with a population of 12.033 ihhabitants(INEI- 2007); is called"Antorcha del Huallaga",because of its unique characteristic in terms of its . scenic beauty, located in the central part of the region San Martín to 249 meters above sea level has a tropical climate - dry, its temperature is variable between 28° and 33° heat and 18° and 28° of relative humidity, suffering variations in the last years due to the presence of serious negative impacts as the massive deforestation of forests, migration and pollution by waste. Under this scenario, the present work entitled "Characterisation of Solid Waste in the City of Bella vista - 201 O " is the result of an investigation and determination of the physical characteristics ofthe solid waste generated in the cityofBellavista. Covers issues of generation per-capita, density, physical composition and volume of solid waste from different sources ( domestic, foreign businesses, institutional, markets and flea markets). The investigation is complemented by a survey of the habits and attitudes of the users of the municipal existing system. On the basis of this information is presented a series of conclusions, it makes severa! recommendations. Even when it is known that each municipality ofthe country has its own reality, the present study is an example methodological that can serve as a guide in similar studies on any part of the country. The characterization of so lid waste from the city of Bella vista, has allowed us to reach the conclusion that the total volume of the solid waste generated in the city is: 45.39 m3, with which it is recommended to begin the development of a comprehensive plan for environmental management of so lid waste, consider the design of the routes of collection, education and environmental awareness, closure of the existing dump and location in a suitable place to dispose ofwaste solids (a sanitary landfill). Key words: solid waste, environmental management.